Assessment beliefs and practices of Libyan Secondary School English language teachers - Nimehchisalem, Vahid; Abdalla, Marwa M. (Australian International Academic Centre, 2020)
Despite the increasing concerns about the importance of assessment, the studies that directly address the assessment beliefs and practices among Libyan secondary school English language teachers are scarce. The present study aimed to investigate the Libyan teachers’ classroom based assessment beliefs and practices and the relationship between them. For this purpose, a total of 90 Libyan English teachers participated in a survey by responding to a questionnaire which explored their beliefs and practices in the four stages of assessment; namely, planning, implementing, monitoring and recording. Based on their perceptions, other than their confusion over ethical matters in assessment, the teachers’ beliefs and practices generally seemed to be at an acceptable level. The results also demonstrated that the relationship between teachers’ beliefs and practices is positively moderate and significant in all stages of assessment. The findings are expected to provide insights into the difficulties encountered by the language teachers and learners in the assessment processes, and therefore, enhance assessment practice and learning conditions.